2019
DOI: 10.1111/acem.13682
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Ocular Ultrasound for the Diagnosis of Retinal Detachment: A Systematic Review and Meta‐Analysis

Abstract: Background: Ocular complaints are common presentations to the emergency department (ED). Among these, retinal detachment can cause significant vision loss if not rapidly diagnosed and referred for appropriate treatment. Point-of-care ultrasound has been suggested to identify the diagnosis rapidly when the ocular examination is limited or the ophthalmology service is not readily available. However, prior studies were limited by small sample sizes, resulting in wide ranges of potential accuracy. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 35 publications
3
31
0
1
Order By: Relevance
“…This resulted in the exclusion of 5 studies of radiologist-performed POCUS included in the systematic review by Gottlieb and colleagues, 14 which included a wide range of POCUS operators assessing for retinal detachment. Nonetheless, our results were consistent with those reported by Gottlieb et al 14 In addition, we found good-to-excellent diagnostic accuracy in assessing for vitreous hemorrhage, lens dislocation, intraocular foreign body, and globe rupture, although the 95% CIs around some of our results are wide. Interestingly, POCUS appears to be less accurate in diagnosing vitreous detachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the exclusion of 5 studies of radiologist-performed POCUS included in the systematic review by Gottlieb and colleagues, 14 which included a wide range of POCUS operators assessing for retinal detachment. Nonetheless, our results were consistent with those reported by Gottlieb et al 14 In addition, we found good-to-excellent diagnostic accuracy in assessing for vitreous hemorrhage, lens dislocation, intraocular foreign body, and globe rupture, although the 95% CIs around some of our results are wide. Interestingly, POCUS appears to be less accurate in diagnosing vitreous detachment.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis 14 demonstrated sensitivity and specificity of 94% and 96%, respectively, for ocular POCUS to diagnose retinal detachment. The meta-analysis 14 included studies of POCUS performed by a range of practitioners, including radiologists and ophthalmologists, and included a total of 844 patients from 11 studies. Subsequently, 2 large, prospective studies 15,16 have added substantially to the existing data regarding EP-performed ocular POCUS.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility of US is extensive; see Table for a list of clinical conditions that potentially can be ascertained with US. For example, appropriately trained emergency physicians can effectively use US to accurately diagnose the conditions of patients who present to the emergency department, including those with conditions related to early pregnancy, possible pericardial effusion, abdominal aortic aneurysm, undifferentiated shortness of breath, and vision loss with retinal detachment and those patients who have been traumatically injured . The ability to perform and interpret these US examinations allows clinicians to diagnose potentially life‐threatening conditions in a timely manner.…”
Section: Point‐of‐care Ultrasound Patient Examinationsmentioning
confidence: 99%
“…5 Accuracy for RD was much higher in the trainees and the EPs who enrolled 3 or more patients, possibly reflecting a higher level of training. In 2019, Gottlieb et al 6 published the largest systematic review and meta-analysis to date, to my knowledge, examining ocular POCUS for RD, including the study by Kim et al 5 and 10 other studies, with 844 total patients. In the 5 ED studies, ocular POCUS had a pooled sensitivity of 92% (95% CI, 67%-99%) and specificity of 91% (95% CI, 85%-95%).…”
Section: 2%-982%)mentioning
confidence: 99%